KEHIDUPAN SOSIAL EKONOMI BOS TAMBANG PASIR (2000-2010). - Wanjoni, Heris; Naldi, Hendra; Yulia, Refni (Pendidikan Sejarah, 2014)
Socio-Economic life the Boss of sand mine . History Education Program. STKIP PGRI West Sumatra. Padang 2014. This thesis discusses the changes of Social Life the boss of sand mine in Nagari Pasir Talang, Sub-district Sungai Pagu Regency Solok Selatan Province West Sumatera. The changes of social life directed to the boss of sand mine in Nagari Pasir Talang Sub-district Sungai Pagu. The purpose of this research is to explain what are the changes that happened in social life the boss of sand mine in Nagari Pasir Talang. Life the of boss sand mine in Nagari Pasir Talang, the influence the of boss sand mine on social economic life of boss sand mine in Nagari Pasir Talang Sub-district Sungai Pagu Regency Solok Selatan in 2000-2010. The method that used in this study is the historical method. The method consists of the following four stages: (1 ) Heuristic is a collect the data , looking for the source and conclude to library study and interviews . ( 2) Criticism source , in order to obtain the facts of history . ( 3 ) Interpretation, the obtained data analyzed and interpreted with connecting and comparing the observed facts so the fact that ready to be served . ( 4 ) Historiography,Â  writing in the form of scientific papers after collect the data and facts that really accurate and valid then write in the form of a thesis . This study describes the life the boss of sand mine changes which previously worked as a farmer turned into a boss of sand mine. During they be a farmer their income just enough for daily needs. However, after 2000 when they switched into of the sand mine, their socio-economic life is growing until 2010. Increased socio-economic life boss of sand we can see from the previous income which just enough for daily need, but after be a boss of sand mine they can sufficient their family life, such as lifestyle, education, housing and health care.